2021
DOI: 10.1038/s41598-021-83694-z
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning aided interpretable model for rupture strength prediction in Fe-based martensitic and austenitic alloys

Abstract: The class of 9–12% Cr ferritic-martensitic alloys (FMA) and austenitic stainless steels have received considerable attention due to their numerous applications in high temperature power generation industries. To design high strength steels with prolonged service life requires a thorough understanding of the long-term properties, e.g., creep rupture strength, rupture life, etc., as a function of the chemical composition and processing parameters that govern the microstructural characteristics. In this article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In our data sets, tree-based ensemble type models perform better than other models to predict Young's modulus. Ensemble type algorithm showed better performance in other studies to predict materials properties 34,48,49 . Ensemble methods are meta algorithms that combine several base models to produce a better predictive model.…”
Section: Resultsmentioning
confidence: 93%
“…In our data sets, tree-based ensemble type models perform better than other models to predict Young's modulus. Ensemble type algorithm showed better performance in other studies to predict materials properties 34,48,49 . Ensemble methods are meta algorithms that combine several base models to produce a better predictive model.…”
Section: Resultsmentioning
confidence: 93%
“…Friedman [43] proposed the gradient boosting machine as a simple and highly flexible machine learning tool. It is a widely used machine learning algorithm that has been shown to be effective in a variety of applications [44][45][46]. The basic idea behind GBM is to build a prediction model using a set of poor learning algorithms, most commonly decision trees.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…The data used in this study were collected over 30 years of concerted efforts from government and non-government initiatives 16 . The overarching goal of probabilistic machine learning is to make reliable predictions for unknown alloys as well as to accelerate the data collection process to improve the model performance.…”
Section: Resultsmentioning
confidence: 99%
“…Neural Network has been successfully employed in the past by Cole et al 12 and Brun et al 13 to model the creep rupture strength from physical and processing parameters. In a recent article, it was shown that a Gradient Boosting Algorithm 14 can be used to efficiently predict the rupture life 15 and rupture strength 16 of 9–12 wt% Cr ferritic-martensitic steels and austenitic stainless-steels. However, oftentimes the prediction is unreliable for low confidence modeling, where the data is either scarce and highly non-linear or the uncertainty associated with the prediction is not available.…”
Section: Introductionmentioning
confidence: 99%